Characterization of the predominant wind speed and direction in Santa Catarina, Brazil - Wahrlich, Júlia; Silva, Flávia Arcari da; Campos, Claudia Guimarães Camargo; Rodrigues, Maria Laura Guimarães; Medeiros, Jéssica (Revista Brasileira de Climatologia, 2021)
Although the state of Santa Catarina has little variation in latitude, it presents significant spatial variations in its climate. Wind is considered an important meteorological variable, but it is not intensively studied and there is a shortage of information on this subject in the region of Santa Catarina. Thus, the objective of this article was to analyze the behavior of the winds in five regions of the state, with different aspects. For that, daily data from National Institute of Meteorology of direction and speed of the winds were used from 1974 to 2016. The conventional meteorological stations used were: Chapecó, Campos Novos, Lages, Indaial and Florianópolis. Regarding wind speed, Florianópolis and Campos Novos registered the highest speeds during the whole year. In the analysis of wind direction, the prevalence of South Atlantic subtropical anticyclone was observed in most of the year in Forianópolis (circulation going north), Lages and Campos Novos (turning northeast) and Chapecó (predominant wind direction in the este). For Indaial, the prevalence was the effect of the valley-mountain breeze.